Optimization and Control Strategies for Mechanical Vehicle Trajectory Research - Ji, Mutong (Transactions on Computer Science and Intelligent Systems Research, 2024)
With the rapid advancement of contemporary transportation and automation technology, the optimization of mechanical vehicle trajectories and control strategies have gradually become a focal area of research. Precise trajectory optimization not only enhances the driving efficiency of vehicles but also significantly reduces energy consumption and safety hazards. This paper reviews the basic theory of mechanical vehicle motion trajectories, focusing on the methods of trajectory optimization and control strategies. It covers model-based trajectory optimization, data-driven optimization methods, and various control strategies. Through an analysis of existing research, it points out the challenges and prospects of applying trajectory optimization and control strategies in complex environments.